An Adviser for cataloguing conference proceedings: design and development of CoPAS - De Silva, S.M.; Zainab, Awang Ngah (Taylor & Francis, 2000)
This article describes the design and development of an expert adviser to catalogue published conference proceedings. The Conference Proceeding Adviser System (CoPAS) was designed to educate novice cataloguers in creating bibliographic records for published conference proceedings as well as to improve conventional instruction in the cataloguing of conference proceedings. The development tool was Asymetrix ToolBook II. The knowledge base of the expert system was in the domain of cataloguing published conference proceedings and consists of public and private knowledge. Public/published knowledge are the relevant AACR2R rules that were identified based on the nine types of published conference proceedings. Private knowledge or heuristics was elicited from three human expert cataloguers through a multiple-observation approach. The elicited personal knowledge was then modelled into a mental map of their thought processes on how to provide a bibliographic description for published conference proceedings. Based on the mental mapping of the experts, the expert adviser system was designed and developed.